AN APPROACH TO THE EVALUATION OF RE-FUNCTIONED HISTORICAL BUILDINGS IN VIEW OF NATURAL LIGHTING, A CASE STUDY IN DIYARBAKIR TURKEY - Aykal, Demet; Gumus, Bilal; Unver, Rengin; Murt, Ozgur (ZNACK PUBLISHING HOUSE, 2011)
Today, re-functioning cultural heritage by preserving the buildings within the scope of historical heritage is one of the most important issues in the area of cultural heritage management. The re-functioning should be adapted to the building so that it reflects and conserves the original functions. Natural lighting is also an important parameter in such re-functioned buildings. In this study, an approach is introduced for evaluating re-functioned historical buildings in terms of natural lighting. Data for evaluating the original and new functions of historical structures in terms of natural lighting are proposed. As an example of this evaluation approach, three re-functioned historical buildings in Diyarbakir Historical Housing Texture have been examined in terms of natural illumination. The evaluation process and the results were obtained in different months, seasons and also different weather conditions for the Cahit Sitki Taranci House in Diyarbakir. The house studied within the context of this case study using the proposed approach is presented in this article.
Keywords: historical structure; new-functioning; natural lighting; illumination level; diyarbakir historical housing texture; Engineering; Optics